The relationship between menstrual cycle characteristics, premenstrual syndrome prevalence and blood phenylalanine level in women with PKU - Arzu Selamioğlu; Zelal Tandoğan; Mehmet Cihan Balcı; Meryem Karaca; Tuğba Kozanoğlu; Alihan Yesil; Gülden Gökçay (Molecular Genetics and Metabolism Reports)
Phenylketonuria (PKU) results from a deficiency in phenylalanine hydroxylase, catalyzing the conversion of phenylalanine (Phe) to tyrosine. Premenstrual syndrome (PMS) consists of physical, behavioral, and emotional symptoms occurring during the last week of luteal phase. The aim of the study was to determine the incidence of PMS, and document menstrual cycle characteristics of PKU patients to reveal the relationship with blood Phe levels. The study was conducted on 74 patients with a mean age of 21.7 ± 5.4 years. The mean age at menarche was 12.7 ± 1.3 years and 82.4 % had regular menstrual cycles. The periods of most patients (47.2 %) lasted 4–5 days. Menstrual cycles of 21–28 days were reported by 73 %, less than 21 days by 8 %, and more than 28 days by 19 % of women. Menorrhagia and dysmenorrhea was observed in 6.7 % and 71.6 % respectively. Adherence to diet was lost in 7 patients during the menstrual period. No significant relationship was found between Phe levels and PMS symptoms (p > 0.05). According to PMSS subscales, 52.7 % of patients with PKU had depressive feelings, 16.2 % anxiety, 55.4 % fatigue, 52.7 % irritability, 28.3 % depressive thoughts, 39.1 % pain, 59.4 % changes in appetite, 28.3 % changes in sleeping habits and 43.2 % had swelling. The findings of the study revealed that PMS prevalence was 39.1 % among PKU women. Awareness about this syndrome, will improve the quality of life in women with PKU by evaluating and taking measures for PMS. Synopsis: Evaluating menstrual cycle characteristics and premenstrual syndrome in phenylketonuria patients provides valuable insights for enhancing their overall health profile and personalizing treatment and management plans.